Pengaruh Latihan Metode Drill Terhadap Ketepatan Shooting Futsal Pemain FORKIP UNIB: The Effect of Drill Method Training on the Accuracy of Shooting Futsal UNIB FORKIP Players - Abima Rizki; Ari Sutisyana; Bogy Restu Ilahi (Universitas Bengkulu, 2023)
Abstrac This study aims to determine the effect of drill method training on the accuracy of shooting futsal for UNIB FORKIP players. This research is a quasi-experimental research. In this experimental study, the sample used was 25 players/students. Based on the results of research and discussion, this study concludes that the effect of drill method training on the accuracy of shooting futsal for FORKIP UNIB players states that the final test with t count is 5.017 from the day of t test and the t table value is 1.713, meaning Ha is accepted, meaning that there is a significant effect, between drill method training on shooting accuracy of UNIB FORKIP futsal players. Keywords: Drill Method Training, Shooting Accuracy, UNIB FORKIP